The Power of the Physics Independent Learning Model Instrument in Online Tutorials to Enhance Independent Learning Skills and Critical Thinking Skills - Pandiangan, Paken (Advances in Social Sciences Research Journal, 2023)
Universitas Terbuka has an especially significant role in seeking quality processes and learning outcomes through valid and effective learning, especially in Open and Distance Learning (ODL). As material for operationalizing the Physics Independent Learning (PIL) learning model in online tutorials, learning instruments for the PIL model are needed so that it supports independent learning skills and critical thinking skill of students at ODL. This study aims to analyze the validity and effectiveness of the PIL model instrument in online tutorials to improve self-learning and critical thinking skills in ODL physics students in wave and sound physics courses. This type of research is educational development research with a sample of 120 undergraduate physics education students at Universitas Tebuka. This research was conducted in two stages , namely preliminary and developmental studies, and extensive trials. The results showed that both the content validity and the construct validity of the PIL model set of wave and sound materials were included in the validity and reliability categories with rα each of (0.800 – 0.936) > (0.2907 - 0.2656) for r table N = (9 - 51) and α are greater than 0.9, respectively. The independent sample t-test parametric inferential statistical test results show that the p value > 0.05. The PIL model instruments of wave and sound materials is consistent with the PIL model, so it is suitable for use in physics learning tutorials. The PIL model instrument is effectively used in learning physics because it can have a consistent impact on improving student learning outcomes in the CTS and ILS aspects on large-scale tests. Obstacles that previously appeared in ODL such as limited practice tools and materials as well as limitations in independent learning and critical thinking skill, can be overcome through the PIL model instruments. The PIL model set is recommended to support students' independent learning and critical thinking skills in ODL.